The Effect of Matlab Software Mastery on The Students’ Learning Motivation of Linier Equation and Matrix Materials - Nur Yuliany; Suharti Suharti; A. Sriyanti (Alauddin Journal of Mathematics Education, 2019)
The study aimed to determine the effect of motivation on the learning outcomes of linear equation and matrix materials by using Matlab software. This study was an ex-post facto quantitative research. The sampling technique used is simple random sampling. The descriptive test results showed that the average student learning motivation score was 61.46 which means that the learning motivation score was in the moderate category in general, while the mean value for the linear equation and matrix materials of the students learning outcomes was 69.29 which meant that the mathematics learning outcomes were in the medium category, while the inferential test results by using the results of regression test analysis proved that the regression equation obtained was . From the results of the significant test, it was obtained the significant value as many as , the result from the significant value , so that H0 was accepted. It could be inferred that there was significant effect on the learning motivation by using Matlab software toward the students’ learning outcomes of linear equations and matrix materials.